The Symbolic Expression of Black American In Langston Hughes’ Poem ‘’Freedom’s Plow’’ - Rasiah Rasiah; Ansor Putra; Irfan Irfan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
Langston Hughes is a black American poet who strived to express the experiences of Black in the United States. One of his poem is Fredom Plow which utilized through lots symbols that refered to the problem of discrimination and the vision of American as a nation. This study is aimed to analyze the expression of Black American expression in Freedom’s Plow poem. This study used semiotics approach in analyzing research data by adopting model proposed by C.S Pierce. There are three types of signs based on the relationship between the sign and the signified, namely; Icons, Index, and symbols. Based on the semiotics frameworks, this study found that  Langston Hughes harneses the signs to express (1) preserverance of black to get freedom, (2) expossing the contradiction of American democracy, and (3) the expression of togetherness and unity